Suboptimal vaccination rates in rural Ghana despite positive caregiver attitudes towards vaccination. Issue 2 (2014) - Ansong, Daniel; Tawfik, Daniel; Williams, Emmanuel Ato; Benson, Scott; Nyanor, Isaac; Boakye, Isaac; Obirikorang, Christian; Sallah, Lorraine; Arhin, Bernard; Boaheng, Joseph Marfo; Amuzu, Evans; Asibey, Osei; et al.
No abstract available